Negotiating International Research Collaborations in Tajikistan. (February 2020) - Sabzalieva, Emma
The fall of the Soviet Union in 1991 heralded not only the creation and opening of borders but also the rapid entry of new actors and ideas into this previously isolated part of the world. This is typified by dramatic increases in the number of international research collaborations involving an ever-growing array of actors. Yet instead of pluralizing knowledge creation and ways of knowing, intensifying processes of globalization have given rise to a "global science" system that has not flattened or significantly altered existing knowledge hierarchies, despite greater diversity in international research collaborations. In the former Soviet state of Tajikistan, this is further tempered by resourcing gaps, political controls, and cultural factors, offering a unique setting through which to explore how researchers negotiate international research collaborations. Centering the perspectives of Tajikistani researchers, the article offers new insights into the reframing of globally homogenizing models of international research collaboration.